Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.5001/omj.2017.92
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Toll-like Receptor 2 and 4 in Peripheral Blood Neutrophil Cells from Patients with Chronic Obstructive Pulmonary Disease

Abstract: The increased expression of TLR2 and TLR4 suggests its role in disease pathogenesis of COPD. Smoke pack years was negatively associated with spirometric parameters in COPD patients. This may help to predict the smokers without COPD who risk developing the condition in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The intrinsically reduced expression of TLRs in COPD patients may also contribute to the impaired pulmonary immune response thus facilitating NTHi persistent colonization. Expression of TLR2 or TLR4 are found to be lower on sputum neutrophils, alveolar macrophages, nasal epithelium, and T cells in COPD patients despite high concentrations of IL-8 and MMP-9 ( 295 298 ).…”
Section: Impaired Immunity In Copd In Response To Nthi Infection—currmentioning
confidence: 98%
See 1 more Smart Citation
“…The intrinsically reduced expression of TLRs in COPD patients may also contribute to the impaired pulmonary immune response thus facilitating NTHi persistent colonization. Expression of TLR2 or TLR4 are found to be lower on sputum neutrophils, alveolar macrophages, nasal epithelium, and T cells in COPD patients despite high concentrations of IL-8 and MMP-9 ( 295 298 ).…”
Section: Impaired Immunity In Copd In Response To Nthi Infection—currmentioning
confidence: 98%
“…Inversely, peripheral blood neutrophils isolated from COPD patients have increased expression of TLR2, TLR4, and NLRP3 ( 298 , 300 ). Nevertheless, the increased TLRs expression might not improve the microbicidal ability of COPD peripheral neutrophils probably due to the inaccurate responses to cytokines ( 179 ).…”
Section: Impaired Immunity In Copd In Response To Nthi Infection—currmentioning
confidence: 99%
“…A number of researchers have demonstrated that the effect of LPS on neutrophils from smokers with COPD results in an increase in TLR2/ TLR4 expression and a subsequent enhancement of the synthesis of IL-8 and matrix metalloproteinase-9 (MMP-9). 10,44 It has been revealed that TLR9 can also contribute to the cigarette smoke-mediated neutrophilic response by providing IL-8 secretion from circulating neutrophils. 4 Apparently, an enhanced blood neutrophilic response in COPD can be triggered by both bacterial or viral infection and cigarette smoke.…”
Section: Tlr2 and Tlr4 In The Development Of Copd Exacerbationmentioning
confidence: 99%
“…Neutrophils are the dominant circulating leukocyte. Bacterial extract, LPS, induces peripheral circulating neutrophils from COPD patients to secrete higher amounts of IL-8/CXCL8 ( 20 , 21 ) as well as matrix metalloproteinase 9 ( 21 ). Moreover, several studies suggested that neutrophils from COPD patients display increased migration toward inflammatory stimuli ( 22 , 23 ).…”
Section: Innate Immune Systemmentioning
confidence: 99%